UJI PERFORMA DEKSTRIN-GUM ARABIC SEBAGAI FILLER VIRGIN COCONUT OIL (VCO) - Y. Wuri Wulandari, Akhmad Mustofa & (Eksplorasi, 2008)
Virgin Coconut Oil (VCO) is one of coconut product that is produced by cold processing. Quality of VCO decrease by oxidation if this product stored in long periode.VCO is not delicious product to be consumpted by everyone. An oil flavor always prevent someone to consumpt it. Change this product to be a powder (microencapsulation) and then insert it into a capsul will disappear that flavour. This process will maintain the quality of VCO too.The research indicate that best result in microencapsulation is using gum Arabic as filler and 2 liters of etanol for mix VCO with gum Arabic. This formula will maintain lauric acid, as the indication of a good or bad VCO, in a stable contain.Keyword : Virgin Coconut Oil, mikroencapsulation, gum arabic, lauric acid